Seasonal shellfish exploitation by Neanderthals 115,000 years ago - Asier García-Escárzaga; Igor Gutiérrez-Zugasti; Arnaldo Marín; Josefina Zapata; Adolfo Moreno-Márquez; Leon J. Clarke; Stefania Milano; Gernot Nehrke; Ronald Castellón-Vargas; Patrick Roberts; João Zilhão; André C. Colonese (Proceedings of the National Academy of Sciences, 2026)
The southern coast of Europe has been at the center of archaeological debates contrasting the social and cognitive capabilities of Neanderthals and modern humans. Early evidence of marine resource exploitation by Neanderthals in this region challenged some views that coastal adaptation was a trait distinctive of modern human cognition and behavior. While it is now evident that Neanderthals exploited marine resources, the nature of their seasonal foraging strategies remains an open question. Here, we analyzed the oxygen isotope composition of mollusk shells collected by Neanderthals at Los Aviones Cave (Iberian Peninsula), demonstrating that they primarily exploited intertidal mollusks during the colder months of the year. This harvesting pattern anticipates the dominant seasonal exploitation strategies observed among later modern human populations in southern Europe, highlighting a degree of behavioral flexibility in Neanderthal use of coastal ecosystems.